Concentrations of Heavy Metals in Three Brown Seaweed (Phaeophyta: Phaeophyceae) Collected from Tourism Area in Sanur Beach, Coast of Denpasar, Bali and Public Health Risk Assessment - I Wayan Rosiana; Putu Angga Wiradana; Anak Agung Ayu Putri Permatasari; Yesha Ainensis El G. Pelupessy; Matius Victorino Ola Dame; Agoes Soegianto; Bambang Yulianto; I Gede Widhiantara (Jurnal Ilmiah Perikanan dan Kelautan, 2022)
Highlight Research Brown seaweed heavy metals content varies between species Risk assessment showed low health risk for heavy metal from intake of the three brown seaweed The three types of brown seaweed did not show carcinogenic properties to metal Arsenic (As) Abstract Marine brown seaweed are known as one of the potential biological agents to be developed as functional food and medicinal sectors. This study aims to examine the concentration of heavy metals (Pb, Cd, Hg, and As) in brown algae (Sargassum aquifolium, Padina australis, and Turbinaria ornata.) and the possible exposure to health risks caused by consumption.  Heavy metal concentrations were determined using Atomic Absorption Spectroscopy (AAS) on brown seaweed samples obtained from three different sites. The average concentration of heavy metals in the dry weight of brown seaweed remains within the guidelines established by The Food and Drug Supervisory Agency (BPOM) Number 32 of 2019 concerning the Safety and Quality of Traditional Medicines, which is then used to calculate the estimated daily intake (EDI), target hazard quotient (THQ and TTHQ), and target cancer risk (TCR) for arsenic associated with food exposure to potentially toxic metallic elements. Each species of brown seaweed has a THQ and TTHQ level of <1, indicating that one or more toxic metal elements in the same meal provide no significant non-carcinogenic risk. The TCR for arsenic in these seaweeds are all less than 1 x 10-4, indicating no cancer risk. There are no chronic health hazards related with the ingestion of brown seaweed harvested from the coast of Sanur Beach at Denpasar, Bali.